Pariwisata Halal: Studi Komparatif Hotel Syariah di Yogyakarta dan Bali - Abd. Halim; Nurdhin Baroroh (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2021)
In recent years, the hotel business has become a leading sector in the development of the halal industry. This makes hoteliers compete to provide excellent service for Muslim tourists. This phenomenon received a positive response from the government with the issuance of the Minister of Tourism and Creative Economy Regulation No. 2 of 2014 concerning guidelines for the implementation of a sharia hotel business. This paper attempts to describe the response of hoteliers in Yogyakarta and Bali to ministerial regulation. The results of this study conclude that hoteliers in Yogyakarta respond to these regulations by choosing the concept of a sharia hotel, namely hotel management in accordance with the provisions of Islamic law; while hoteliers in Bali choose the concept of a Muslim-friendly hotel, namely a hotel with Islamic characteristics that is able to provide basic facilities that are more friendly to Muslim customers.